Performance enhancement of distance relay in presence of unified power flow controller - Hiba Nadhim A. Al-Kaoaz; Ahmed Nasser B. Alsammak (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
The characteristics of the distance relay are devised based on online and fault impedance. The relay uses fault information to react to the expected state; however, integrating the grid with a unified power flow controller (UPFC) might stop the relay from fault-triggered operations, requiring altered relay characteristics. Building relay tripping parameters are among the critical challenges that must be addressed for transmission line distance relays because current transmission networks face higher stress regarding power system operation. Furthermore, the use of flexible AC transmissionÂ systems (FACTS) instruments at the transmission level adversely affects distance relay performance due to impedance differences. The UPFC is among the essential FACTS instruments; it comprises shunt and series converters to alter the apparent relay impedance; hence, it was considered for this study, where a test system during fault was assessed to demonstrate the output of the distance relay before and after using the UPFC. MATLAB was used to build scenarios demonstrating the effect of a UPFC located in the transmission line's midsection or end or not using the UPFC. This research offers an analytical technique to determine the probable effects of UPFC on distance relay characteristics. The outcomes provide new relay characteristics for several fault resistances and locations for fault-specific impedance trajectory reactions.